An Exceptional Case of Expedited Recurrence and Progression of Granular Cell Ameloblastoma: Extension to the Temporal Bone - Varshney, Anchal; Madhur, Madhur; Gopal, Lipika; Bhargava, Manish; Tanwar, Indu (Journal of Neonatal Surgery, 2025)
Odontogenic tumors are any abnormal growth in and around the mandible and teeth. Ameloblastoma is an aggressive odontogenic tumor of the mandible. Its extensive tumefaction accords to a high malignant transformation potential. Asymptomatic slow growth of the affected area is a consensus in the literature for the manifestation of ameloblastoma which is consistent. It comprises nearly 1% of all oral tumors, 13-58% of all odontogenic tumors, and is far more typical indeveloping countries with an elevated risk of recurrence. Granular cell ameloblastoma (GCA) is a less prevalent histological subtype of ameloblastoma with a pronounced transformation of the cytoplasm of stellate reticulum like cells into a rough, granular eosinophilic appearance. This article reports a case of GCA involving the posterior part of the right mandible region in a 37-year-old female patient which even after surgical resection recurrence and spread to the frontal bone.